Pengaruh Laju Aliran Dan Ukuran Umpan Sisa Hasil Pengolahan Dengan Humprey Spiral Pada Skala Laboratorium Kabupaten Bangka - Suryani Suryani; Franto Franto; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2022)
Remaining Processing Results is a combination of grains measuring 0.001-0.6 mm and still has an economical concentrate content. Humphrey Spiral contained in PT Bumako produces cassiterite concentrate content of 2%, while the company's target concentration is 10%. So, a research was conducted on the Humphrey Spiral on a laboratory scale to determine changes in concentrate levels and cassiterite recovery, with flow rate parameters with variations of 1.017 m/s, 1.097 m/s and 1.172 m/s and feed sizes, namely 60 mesh, 80 mesh and 100 mesh. This research method uses Grain Counting Analysis (GCA) and XRF. Based on the results of the study, the accompanying minerals in the Humphrey Spiral bait consisted of 83.98% quartz, 5.65% limonite, 5.19% hematite, 2.83% iron oxide, 1.73% monazite, 0.34% chalcopyrite, magnetite 0.17% and muscovite 0.10%. The highest concentration gain and concentrate recovery was at a speed of 1.097 m/s at a grain size of 100 mesh with a content of 10.3788% and a high recovery of 44.1512%.